TINGKAT KOMPETENSI KEPRIBADIAN KONSELOR DITINJAU DARI MASA KERJA DAN LATAR BELAKANG PENDIDIKAN - Hikmah, Muttakhidatul (Indonesian Journal of Guidance and Counseling: Theory and Application, 2014)
The purpose of this research to is generate data on personal competence level counselors in Semarang state high schools in implementing guidance and counseling services, and Â whether there are differences by terms of services and educational background. The population of this study is Semarang state high school counselors. Data collection methods used is a psychological scale with personal competence counselors scale as an instrument. Data analysis technique used is descriptive-percentage analysis technique. The results of this study indicate that personal competence level of Semarang state high school counselors in implementing guidance and counseling services are in the high category (74,35%), and there are differences on personality competence counselor in Semarang state high schools in implementing guidance and counseling services by terms of services and educational background.